PENGARUH TINGKAT FUNGI MIKORIZA ARBUSKULA TERHADAP PRODUKTIVITAS RUMPUT GAJAH MINI (Pennisetum purpureum schamach ) PADA TANAH ULTISOL - reza prabudi (Jurnal Peternakan Integratif, 2014)
ABSTRACT This study aimed to examined the growth of Mini Elephant Grass             (Pennisetum purpureum schamach) on the ultisol by utiliting different levels of mycorrhiza  arbuscular (FMA). The experiment was conducted at the Agricultural Faculty, Universitas Sumatera Utara started on October 2012 to February 2013. The design used in the study was completely randomized design ( CRD ). Treatments consists of level mycorrhizal arbuscular P0 = 0 g FMA/polybag ( control ), P1 = 10 g FMA/polybag, P2 = 20 g FMA/polybag and P3 = 30 g FMA/polybag . The variable were  studied were plant height, number of tillers, fresh production, dry matter production, and root biomass of  Mini Elephant Grass (Pennisetum purpureum scamach).The results showed that the highest high grass was in treatment                  P3 (135.00 cm) and the lowest was in treatment P1 (105.60 cm), the  highest number of grass tillers was in the treatment P2 and P3 (12.60 clumps) and the lowest was in treatment P0 (6.80 clumps),  the highest fresh production of grass was in treatment  P3 (238.08 g) and the lowest was in treatment  P0 (193.84 g), the highest dry matter production was in treatment of P2 (25.22 g) and the lowest was in treatment P1 (17.30 g), while for the highest roots biomass  of grass was in treatment  P3 (111.33 g) and the lowest was in the P0 treatment (46.95 g ). The conclusion was level mycorrhiza arbuscular in treatment P3 ( level 30 g / polybag ) showed the best results in productivity mini elephant grass ( Pennisetum purpureum schamach ). While the treatment P0 ( control ) showed the worst results in productivity mini elephant grass ( Pennisetum purpureum schamach ) during the study. Keywords : Mini Elephant Grass,  Mycorrhiza  Arbuscular, Ultisol , Mini Elephant Grass Productivity